Calices et patenae funerales and the Medieval Church of St John at Bribir - Milošević, Ante (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić's 70th birthday, 2020)
The reason that motivated the discussion presented in this paper were the findings of chalices and patens recovered from medieval burials on the site Bribirska Glavica (antique Varvaria, medieval Breberium). To this discussion other similar findings from the territory of Middle Dalmatia are added, indicating that this was in fact practice that can be observed in other parts of Europe in the same period and that it was mostly connected to the burials of distinguished clerics. The chalices and patens from Bribir are explained using similar analogies and because they were found within religious architecture, it is assumed that important ecclesiastical figures were also included in those burials. This contributes to the development of the discussion about the chronology of the church of Sts Joachim and Anne, today used by the Serbian Orthodox Church. So far its chronological span was rather wide, but based on the lastest archeological excavations of the church and its surroundings, we can conclude that it was a part of the medieval abbey of St John the Evangelist, known to us from the historical sources, and that it was built during the first half of the 14th century on the foundations of the earlier Late Antique and Early Medieval octofoil rotunda. Moreover, we also established that it served as a funerary church of the one of the branches of the powerful Šubić-Bribirski noble house.